A prospective study on the prescription pattern of anti-cancer drugs and adverse drug reaction in a tertiary care hospital - Guduru, Harshendra; Jeevanagi, Santosh Kumar R.; Nigudgi, Shantiling; Bhandare, Smita V. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Cancers is a group of disease involving abnormal cell multiplication with the ability to spread to other parts of the body. Common side effects seen with chemotherapy are fatigue, hair loss, easy bruising and bleeding, infection, anemia, nausea and vomiting, appetite changes, constipation etc. The need of this study is to evaluate the prescribing pattern and the adverse drug reaction associated with chemotherapeutic drugs. The study is aimed to analyze the prescribing pattern of anticancer drugs in medical oncology department of a tertiary care hospital, Karnataka. Methods: An observational study was conducted on 30 patients of either sex admitted for chemotherapy for a period of 6 months in at HCG Cancer Institute, Gulbarga and Basaveshwar Teaching and General Hospital (BTGH), Gulbarga. The data collected is analysed statistically using descriptive statistics and presented as counts and percentages. Results are depicted in the form of tables. Results: A total of 30 prescriptions were collected with 10 (33.3%) male and 20 (66.6%) female. the maximum number of cases were noted in the age group of 46years to 55 years (10) and least in age group of 15-25 years having a single patient. In our study we found that more number of patients are breast cancer (12 patients) followed by cervical cancer and ovarian cancer (3 patients) and least are Ewing’s sarcoma and Non-Hodgkin’s lymphoma (1 patient). Most commonly prescribed anti-cancer drug is carboplatin and paclitaxel i.e. for 12 patients out of 30 patients, followed by cyclophosphamide for 10 patients and less commonly prescribed drug being dactinomycin and pemitrexate. Adverse drug reactions seen in maximum patients is hair loss among 20 pts followed by peripheral neuropathy (17) and taste change (16) and the less commonly noted side effects being chest pain and ototoxicity. Conclusions: The study concluded that the drugs which were used in the treatment of various neoplastic conditions are in adherence and in accordance with the standard treatment guidelines and most of them were prescribed with generic name which leads to reduce in cost of treatment.